Microsurgery Simulator of Cerebral Aneurysm Clipping with Interactive Cerebral Deformation Featuring a Virtual Arachnoid. Issue 5 (1st August 2017) - Shono, Naoyuki; Kin, Taichi; Nomura, Seiji; Miyawaki, Satoru; Saito, Toki; Imai, Hideaki; Nakatomi, Hirofumi; Oyama, Hiroshi; Saito, Nobuhito
Abstract: BACKGROUND: A virtual reality simulator for aneurysmal clipping surgery is an attractive research target for neurosurgeons. Brain deformation is one of the most important functionalities necessary for an accurate clipping simulator and is vastly affected by the status of the supporting tissue, such as the arachnoid membrane. However, no virtual reality simulator implementing the supporting tissue of the brain has yet been developed. OBJECTIVE: To develop a virtual reality clipping simulator possessing interactive brain deforming capability closely dependent on arachnoid dissection and apply it to clinical cases. METHODS: Three-dimensional computer graphics models of cerebral tissue and surrounding structures were extracted from medical images. We developed a new method for modifiable cerebral tissue complex deformation by incorporating a nonmedical image-derived virtual arachnoid/trabecula in a process called multitissue integrated interactive deformation (MTIID). MTIID made it possible for cerebral tissue complexes to selectively deform at the site of dissection. Simulations for 8 cases of actual clipping surgery were performed before surgery and evaluated for their usefulness in surgical approach planning. RESULTS: Preoperatively, each operative field was precisely reproduced and visualized with the virtual brain retraction defined by users. The clear visualization of the optimal approach to treating the aneurysm via an appropriate arachnoid incision was possible with MTIID. CONCLUSION: A virtual clipping simulator mainly focusing on supporting tissues and less on physical properties seemed to be useful in the surgical simulation of cerebral aneurysm clipping. To our knowledge, this article is the first to report brain deformation based on supporting tissues.